Suplementação de glicosaminoglicanos na ração de frangos de corte - Martins, Julyana Machado da Silva (2018)
Two experiments were carried out to evaluate performance, hematology and serum biochemistry, locomotor problems, bone and cartilage development, and nutrient metabolizability of broilers supplemented with glycosaminoglycans on ration. The first experiment was conducted in completely randomized design, in a 3 x 3 factorial scheme (three levels of chondroitin sulfate: 0, 0.05, 0.10%, and three levels of glucosamine sulfate: 0, 0.15 and 0.30%), each treatment with six replicates of 30 birds. It was evaluated variables of performance, gait score, valgus and varus, hematology and serum biochemistry, carcass yield, femoral degeneration, tibial dyschondroplasia, macroscopy of tibia and articular cartilage, bone densitometry and strength, bone mineral profile, chondrocyte number, proteoglycans and type II collagen detection tibia articular cartilage, and gene expression of MMP-9 metalloproteinase and its inhibitor in femur articular cartilage. Glucosamine sulfate supplementation increased weight gain at 35 and 42 days old (p = 0.0470 and p = 0.0385, respectively). Chondroitin and glucosamine sulfates reduced the frequency of gait score (p = 0.0067 and p = 0.0001, respectively), and valgus and varus (p = 0.0138 and p = 0.0002, respectively). Glucosamine sulfate reduced frequency of femoral degeneration in the right (p = 0.0139) and left (p < 0.0001) femurs and linearly increased (p = 0.0284) the proliferating cartilage area. Interaction (p < 0.05) was observed of sulfates for leukocytes, lymphocytes, triacylglycerols, very low density lipoprotein (VLDL) and total calcium at 21 days; high density lipoprotein (HDL) and ionic calcium at 21 and 42 days; and for phosphorus, chlorides and sodium at 42 days. Chondroitin sulfate increased linearly (p = 0.0099) albumin and quadratic (p = 0.0140) total serum proteins at 21 days, and linearly (p = 0.0012) calcium blood at 42 days. Glucosamine sulfate linearly reduced (p = 0.0237) the chlorides at 21 days and demonstrated a quadratic effect (p = 0.0450) for albumin at 42 days. There was interaction (p < 0.05) of sulfates for tibial length at 21 days, proximal epiphysis width at 21 and 42 days, and epiphysis distal at 42 days, transverse and medial thickness of articular cartilage of proximal epiphysis at 21 days, and distal epiphysis at 42 days. At 42 days, there was a quadratic effect of glucosamine sulfate levels on tibial length (p = 0.0320) and increasing linear on distal articular cartilage weight (p = 0.0322). There was a higher percentage of calcium (p = 0.0009) and phosphorus (p = 0.0007) on tibia at 21 days with inclusion of glucosamine sulfate, as well as interaction (p < 0.0001) of sulfates for calcium at 42 days. There was interaction (p < 0.05) of sulfates for chondrocytes number, collagen type II and proteoglycans at 21 and 42 days, and for MMP-9 genes expression and its inhibitor at 42 days. The second experiment was performed in completely randomized design, was used in a 2 x 2 factorial scheme (two levels of chondroitin sulfate: 0 and 0.10%, and two levels of glucosamine sulfate: 0 and 0.30%), with eight replicates of 10 birds. Performance, feed nutrient metabolization and intestinal histomorphometry were evaluated. At 21 days old, broilers supplemented with glucosamine sulfate presented greater weight gain (p = 0.0229). There was interaction (p < 0.05) of sulfates for the metabolic coefficients of nitrogen, mineral matter and calcium, and for jejunum villi height. It was concluded that supplementation with glucosamine sulfate in broiler ration increased weight gain and stimulated intestinal histomorphometry and together with the chondroitin sulfate improved the locomotion condition and the bony and cartilaginous development. Sulfates alone promoted greater metabolism of minerals.